Stimulation of Children's Art Development: An Analysis of the Influence of Makeup Play Tools - Heldanita, Heldanita; Shafira, Gina (Kiddo: Jurnal Pendidikan Islam Anak Usia Dini, 2025)
This study aims to determine whether there is a significant influence of makeup play tools on the development of children's fine arts at Griya Bina Widya Kindergarten, Griya Bina Widya Unri Housing Complex, Tuah Madani District, Pekanbaru City. This type of quantitative research uses the experimental method one group pretest posttest design. The subjects of the study were teachers and early childhood at Griya Bina Widya Kindergarten, the object of this study was the influence of makeup play tools on the development of fine arts of children aged 5-6 years. The population in this study were children of Griya Bina Widya Kindergarten. The sampling technique used purposive sampling, where the number of samples taken was 9 children. Data collection techniques were observation and documentation. Data analysis used SPSS Ver. 23 with Paired Samples t-test. The results of the study found the following findings: 1) Makeup play tools can be used as a learning medium; 2) Children are able to be more creative; 3) Children are able to explore; 4) Children are able to feel beauty; 5) Children are interested in playing; 6) Children are able to paint in various ways and objects; 7) Children are able to express artistic activities through imagination; 8) Children are able to draw in various forms. The results of the study showed that there was an increase in children's artistic development in Griya Bina Widya Kindergarten by 52.57% with a moderate category with a normalized formula. The results of the t statistical test have a sign value. 0.000 <0.05 with tcount - 42.090 <ttable - 1.79588. So the null hypothesis is rejected and the alternative hypothesis is accepted so that there is an influence of makeup play tools on children's artistic development in Griya Bina Widya Kindergarten.